Document Analysis of English Course Syllabus in Business Administration: A Critical Evaluation of Syllabus Design - Tanti Nur Khasanah; Nanang Heri Setyo Dwi Cahyo; Satriani Satriani; Sri Rachmajanti (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study critically evaluates an English course syllabus for Business Administration Department at a leading Indonesian university, focusing on its alignment with needs analysis and syllabus content. Adopting a qualitative approach, the research integrates document analysis and a structured interview with the syllabus developer to identify strengths, weaknesses, and areas for improvement. The structured interview explored the Present Situation Analysis (PSA) in syllabus implementation, while critical document analysis examined the Target Situation Analysis (TSA) envisioned by the syllabus, enabling the identification of gaps and actionable solutions. Findings reveal that the syllabus relies on outdated needs analysis data, lacks adherence to the ABCD model in learning objectives, exhibits limited diversity in perspectives and examples, and omits operational verbs in learning indicators, resulting in ambiguity and misalignment with students’ practical needs. Additionally, assessments neglect the psychomotor and affective domains, suffer from unclear scoring rubrics, and display inconsistencies in grading criteria, limiting the syllabus's ability to prepare students for real-world business communication demands. This study contributes to educational sciences by underscoring the importance of updated needs analysis and comprehensive curriculum design for improving instructional effectiveness. It offers actionable recommendations for curriculum developers and educators, advocating for General English courses tailored to specific academic and professional contexts. The findings provide a framework for future syllabus development, emphasizing the integration of inclusive content, clear learning objectives, and robust assessment strategies to support higher education practices in addressing the evolving demands of a globalized and diverse student body.